REVOLUTIONIZING HOME SECURITY: A BIOMETRIC AND GSM- ENABLED SMART DOOR LOCK SYSTEM - Muhammad Shahzaib,; Bilal Ahmed,; Amna Sharif, (Spectrum of Engineering Sciences, 2025)
With the rising concerns over security due to increasing crime rates, ensuring the safety of homes, offices and institutions has become a top priority. Traditional security systems often require carrying keys, which pose challenges such as the risk of loss and the added cost of re-fabricating keys. While several studies have explored security solutions, there remains a significant need for further research to develop an effective security system. This paper introduces a smart lock prototype that offers a modern alternative to conventional locking mechanisms by integrating an electro-mechanical system for unlocking doors using passcodes and fingerprints, with real-time status displayed on an LCD. The system is built using an Arduino microcontroller and incorporates a fingerprint scanner, keypad, LCD display, and GSM module to provide user authentication, visual feedback, and instant alert notifications. The prototype supports up to 100 authorized users and is developed at a total cost of under $50, demonstrating both scalability and affordability. The key advantage of this smart lock is its combination of enhanced security, cost-effectiveness and ease of installation, making it a practical and efficient solution for modern security needs.